2000
DOI: 10.1161/01.res.87.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Dependent Modulation of Contractility and Growth in Smooth Muscle of Rat Portal Vein

Abstract: Abstract-Increased intraluminal pressure of the rat portal vein in vivo causes hypertrophy and altered contractility in 1 to 7 days. We have used organ cultures to investigate mechanisms involved in this adaptation to mechanical load. Strips of rat portal vein were cultured for 3 days, either undistended or loaded by a weight. Length-force relations were shifted toward longer length in stretched cultured veins compared with freshly dissected veins, whereas the length-force relations of unstretched cultured vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(113 citation statements)
references
References 32 publications
7
106
0
Order By: Relevance
“…In vascular smooth muscle of KO mice, Cav-2 is also largely absent, Cav-3 is substantially reduced, and no caveolae structures are observed (4,24). We have previously reported that physiological stretch stimulates protein synthesis in the portal vein and that activation of ERK1/2 is a mediator of this effect (3,30). ERK1/2 activation is rapid and transient with a peak at about 5 min following the onset of stretch, correlating with rapid activation of FAK (2).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In vascular smooth muscle of KO mice, Cav-2 is also largely absent, Cav-3 is substantially reduced, and no caveolae structures are observed (4,24). We have previously reported that physiological stretch stimulates protein synthesis in the portal vein and that activation of ERK1/2 is a mediator of this effect (3,30). ERK1/2 activation is rapid and transient with a peak at about 5 min following the onset of stretch, correlating with rapid activation of FAK (2).…”
Section: Resultsmentioning
confidence: 98%
“…E and F: flow-induced Akt (E) and ERK1/2 (F) phosphorylation of carotid arteries, relative to unstimulated contralateral control arteries, were evaluated following 15 min of ϳ19 dyn/cm 2 shear stress (n ϭ 4). *P Ͻ 0.05. course of organ culture, which is found also in the rat portal vein (30), is unclear, but one possible explanation is reorganization of the actin cytoskeleton to accommodate the applied force and normalize tissue stress (2). Differing contents of Cav-1 following culture could not explain this decrease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 The concentrations listed in table 1 are all given in mM, whereas in the referenced articles they are often given in μmole/(g fresh weight), μmole/(g dry weight) or μmole/(g protein). In order to have all those concentrations in mM, we collected values that gave us an idea of the converting factors: we used literature values for the ratio dry weight/fresh weight [55,3,23,36,5,49,9,45,52], cell volumes [34,43,39,13,47,40,7,33], and values for the ratio cytoplasm volume/dry weight [45]. Even though these values were determined for different organisms, the average should be a good approximation.…”
Section: The Steady State Hypothesis and Parameters Of The Modelmentioning
confidence: 99%
“…One vessel that has been extensively investigated is the rat portal vein, in which elevated intraluminal pressure in vivo over a few days causes hypertrophy and increased contractility (16,21). In vitro, portal venous strips kept in organ culture under an applied load developed increased contractility, protein synthesis, and cell cross-sectional area compared with unloaded control strips (40). This model thus allows investigation of the effect of stretch on the pattern of protein expression and its relationship to contractile differentiation.…”
mentioning
confidence: 99%